2008
DOI: 10.1002/oti.252
|View full text |Cite
|
Sign up to set email alerts
|

The cross‐cultural adaptation of the disability of arm, shoulder and hand (DASH): a systematic review

Abstract: A systematic review of cross-cultural adaptations of the Disability of Arm, Shoulder and Hand into other languages was undertaken focusing on the translation and adaptation process, the problems during the translation process and proposed solutions. Nine articles were selected for analysis. All were written in English and addressed the qualitative issues of the cross-cultural adaptation process. The results demonstrated strong evidence that translation, adaptation and technical issues are most influential in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…Alotaibi (2008) carried out a comprehensive review of articles regarding the cross-cultural translation of the DASH questionnaire and found that some items were more difficult to translate than others because of vagueness in explanation, lack of knowledge or understanding and differences in cultural norms. We have identified some of these types of problems with the DASH-JSSH questionnaire.…”
Section: Introductionmentioning
confidence: 99%
“…Alotaibi (2008) carried out a comprehensive review of articles regarding the cross-cultural translation of the DASH questionnaire and found that some items were more difficult to translate than others because of vagueness in explanation, lack of knowledge or understanding and differences in cultural norms. We have identified some of these types of problems with the DASH-JSSH questionnaire.…”
Section: Introductionmentioning
confidence: 99%
“…Fayad et al reviewed 38 shoulder questionnaires (3) and concluded that there is no gold standard for assessing shoulder function outcome. The 3 other published systematic reviews were specific to a population (shoulder/upper extremity disorders in athletes [2] or following trauma [4]) or to a psychometric property (cross-cultural adaptation of the DASH [5]). None of the 4 systematic reviews used multiple raters for critical appraisal or performed a quantitative synthesis of the studies reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…Four other systematic reviews of shoulder disability questionnaires have been published (2)(3)(4)(5). Fayad et al reviewed 38 shoulder questionnaires (3) and concluded that there is no gold standard for assessing shoulder function outcome.…”
Section: Introductionmentioning
confidence: 99%
“…6,7,11 In contrast, the quick administration time of the DASH has been reported in some studies. 12,13 It is however worth exploring the notion of lack of applicability and time constraints associated with using such a rigorous instrument, with wellestablished psychometric properties, in this context. A systematic review of the cross-cultural adaptation of the DASH included only English-language publications (n ¼ 9); 8 of 9 from developed country contexts.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of the cross-cultural adaptation of the DASH included only English-language publications (n ¼ 9); 8 of 9 from developed country contexts. 13 This presents a biased view in research on this topic for developed countries.…”
Section: Introductionmentioning
confidence: 99%